2013
DOI: 10.1007/s00296-013-2733-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of SIGIRR in systemic lupus erythematosus

Abstract: Single immunoglobulin IL-1-related receptor (SIGIRR), which is also known as Toll/interleukin-1 receptor 8, is a member of the interleukin-1 receptor (IL-1R) family. Different from other typical IL-1R superfamily members, SIGIRR seems to exert negatively modulates in immune responses. Several previous studies demonstrated that SIGIRR influences chronic inflammatory or autoimmune diseases, such as intestinal inflammation, rheumatoid arthritis and psoriatic arthritis. Recent work has explored the role of SIGIRR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…These results were consistent with previous studies which suggested that Th17 cells may be involved in the pathogenesis of SLE and LN (22,25). SIGIRR, a negative regulator of the TLR/ILR pathway, has been studied in patients with SLE (27). Studies had revealed that SIGIRR-knockdown mice manifested with diffuse membrane proliferative glomerulone- phritis, macrophage invasion, immune complex deposition and the formation of autoantibodies including rheumatoid factor, anti-double stranded DNA and anti-Sm (15,28,29).…”
Section: Discussionsupporting
confidence: 92%
“…These results were consistent with previous studies which suggested that Th17 cells may be involved in the pathogenesis of SLE and LN (22,25). SIGIRR, a negative regulator of the TLR/ILR pathway, has been studied in patients with SLE (27). Studies had revealed that SIGIRR-knockdown mice manifested with diffuse membrane proliferative glomerulone- phritis, macrophage invasion, immune complex deposition and the formation of autoantibodies including rheumatoid factor, anti-double stranded DNA and anti-Sm (15,28,29).…”
Section: Discussionsupporting
confidence: 92%
“…SIGIRR deficiency was associated with exacerbated inflammatory and immune reactions under a variety of conditions (Molgora et al 2017). Previous studies have demonstrated that SIGIRR influences chronic inflammatory or autoimmune diseases, such as intestinal inflammation, systemic lupus erythematosus, and psoriatic inflammation, by regulating the activities of NK cells, CD8 T cells or γδ T cells (Wang et al 2022;Wang et al 2013;Molgora et al 2017;Xiao et al 2007;Russell et al 2013). Memory CD4 T cells are of great interest in the context of autoimmune diseases because of their long-lived nature, efficient responses to antigens, and unique potential to mediate recurring autoimmune responses (Raphael et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence proved that SIGIRR could be an essential regulator of inflammation and innate and adaptive immune responses [5][6][7][8][9][10][11][12][13][14][15]. Recent studies have demonstrated that SIGIRR levels are upregulated in PBMCs and synovial cells of RA patients and involved in the pathogenesis of this disease [10,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The interleukin-1 receptor (IL-1R) superfamily includes two subfamilies of IL-1R-like receptors (ILRs) and Toll-like receptors (TLRs); both of which are involved in inflammatory response and innate immunity [ 5 ]. Single Ig IL-1-related receptor (SIGIRR), also named Toll/IL-1 receptor 8 (TIR8) or IL-1R8, is a new member of the IL-1R superfamily [ 6 ].…”
Section: Introductionmentioning
confidence: 99%